CONTEMPORARY APPROACHES TO MALE URINARY INCONTINENCE: A CONTROLLED RANDOMIZED COMPARATIVE STUDY (International Journal of Physiotherapy, 2015)
Background: Urinary incontinence UI is an involuntary leakage of urine due to loss of bladder control which is a common and often embarrassing problem that may cause tremendous emotional distress. Prevalence and risk factors depend on baseline physiological mechanisms, including weakness of pelvic floor muscles, hyperactive bladder that may result in urge UI, poor urethral sphincter function associated with stress UI, and impaired structural and functional integrity of pudendal nerve activity, associated with Pelvic floor muscle weakness plays an important role in UI etiology. Pelvic floor muscles work to support the bladder neck in the intra- abdominal cavity and maintain urinary continence. Weakness of these muscles leads the bladder to shift to the extra-abdominal cavity and thus a change in the urethra-vesicle angle occurs.Methods: Group (A) twenty participants who received behavioral training (BT) pelvic floor exercises (PFE) and interferential current, group (B) twenty participants who received BT, PFE and posterior tibial nerve stimulation, and group (C) twenty participants who received BT, PFE and placebo interferential current. Urodynamic and cystometric measures including bladder volume at first desire to void, maximum cystometric capacity, and pressure at maximum flow rate were measured before and after intervention.Results: Results of this study revealed that there was a statistical significant difference in bladder volume at first desire to void, maximum cystometric capacity, and pressure at maximum flow rate in favor of participants who received a combination of BT, PFE and interferential current compared with those who received a combination of BH and PFE with either posterior tibial nerve stimulation or placebo interferential current.Conclusion: Interferential current is better than posterior tibial nerve stimulation in the rehabilitation of urinary incontinence.